Illicit drug use among students of a university in Southern Brazil - Houvèssou, Gbènankpon Mathias; Bierhals, Isabel Oliveira; Flesch, Betina Daniele; Silveira, Mariângela Freitas da (Revista de Saúde Pública, 2020)
OBJECTIVE: To describe drug consumption and the co-occurrence use of more than one illegal drug as well as associated factors in freshmen at a public university in Southern Brazil. METHODS: Cross-sectional study with census of students entering undergraduate courses in 2017. A total of 1,788 university students answered questions about illicit drug use. For analysis, ordinal logistic regression was used. RESULTS: Marijuana was the most consumed drug (lifetime: 42.1%; 30-day use: 22.7%), followed by hallucinogens (lifetime: 13.1%, 30-day use: 2.8%). Rates for lifetime use of 0, 1 and 2 or more drugs were 56.2%, 23.3% and 20.4%, respectively, and were associated with men (OR = 2.2; 95%CI:1.4–3.5), being at least 23 years old (OR = 2.7; 95%CI: 1.4–5.1), under 18 years old first experimentation with drugs (OR = 2.3; 95%CI: 1.3–3.9) and living with friends (OR = 2.0; 95%CI: 1.2–3.4). Rates for 30-day use of 0, 1 and 2 or more drugs were 76.8%; 18.1% and 5.1%, respectively, and were associated with being single, separated or widowed (OR = 3.2; 95%CI: 1.4–7.0), lower socioeconomic classes (OR = 0.3; 95%CI: 0.1–1.1; p = 0.001), under 18 years old first experimentation with drugs (OR = 1.8; 95%CI: 1.1–2.9) and living with friends (OR = 1.8 95%CI: 1.2–2.8). CONCLUSION: Results indicate that students are at greater risk of illicit drug-related health problems. Thus, a better understanding of this consumption should be pursued, as well as the development of a prevention plan.